Reproductive Technologies and Genomic Selection in Cattle - Patrice Humblot; Daniel Le Bourhis; Sebastien Fritz; Jean Jacques Colleau; Cyril Gonzalez; Catherine Guyader Joly; Alain Malafosse; Yvan Heyman; Yves Amigues; Michel Tissier; Claire Ponsart (Veterinary Medicine International)
The recent development of genomic selection induces dramatic changes in the way genetic selection schemes are to be conducted. This review describes the new context and corresponding needs for genomic based selection schemes and how reproductive technologies can be used to meet those needs. Information brought by reproductive physiology will provide new markers and new improved phenotypes that will increase the efficiency of selection schemes for reproductive traits. In this context, the value of the reproductive techniques including assisted embryo based reproductive technologies (Multiple Ovaluation Embryo Transfer and Ovum pick up associated to in vitro Fertilization) is also revisited. The interest of embryo typing is discussed. The recent results obtained with this emerging technology which are compatible with the use of the last generation of chips for genotype analysis may lead to very promising applications for the breeding industry. The combined use of several embryo based reproductive technologies will probably be more important in the near future to satisfy the needs of genomic selection for increasing the number of candidates and to preserve at the same time genetic variability.